Concordance between dual indirect methods for assessing fat percentage - B. Hurtado; E. Colina; C. H. Gonzalez-Correa (Journal of Electrical Bioimpedance)
In the last decades there is a growing interest in the evaluation of human body composition for being an important part of the integral assessment of individuals. Its use has been extended to different disciplines associated with health care (medicine, nutrition, physiotherapy), and to sports and population fields. Specifically, fat percentage can be related to innumerable diseases. However, there are discrepancies in the results of fat percentage measurement measured by different methods.